Puppet factory a modular and interactive puppet playing kit as a teaching tool for 1st grade teachers and students - Rivera, Mark Gerby L.; Constantino, Nina Elisa B. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2014)
Children go through many transformations throughout their lives, but the most important and crucial transition is when a kid will started to move into grade school. He will be exposed to new and different environmental changes; from a new curriculum which has a higher demand for greater intelligence and work, new sets of subjects, bigger class sizes, to a new method of teaching which can lead to the social stimuli called culture shock. Puppet playing suggests its effectiveness as a teaching strategy and has many advantages. With the help of a puppet play-based teaching tool that deals with interaction and entertainment, there will be a creative and lighter transition while enjoying grade school leading to their next years of undertaking. "Puppet factory" promotes imaginative play which can lead to analytical and critical way of comprehension of 1st grade students.
Thesis (Bachelor of Fine Arts - Industrial Design)--University of the Philippines Diliman
Keywords: Puppet plays; Puppet theater in education